Development of Conceptual Technique by Using Integrated Approaches - Z., Ghazalli; M. M., Noor; Zamzuri, Hamedon (2008)
In order to be a competent player in the market, the product should arrive into market within a short of time and reasonable price. In order to shorten the time to reach the market, most of the manufacturers develop the technique to reduce the assembly cost at the early stage of the design phase. This could be achieve by reducing the part numbers which would reduce the assembly time and assembly cost as well. Design for assembly is one of the techniques that could be adopted by the manufacturers in order to reduce the assembly cost. The objective of this paper is to present the develop methodology which is based on integrated design for assembly technique with other design process. This integrated technique using the philosophy of Theory Inventive Problem Solving (TRIZ), Axiomatic Design (AD) and Boothroyd – Dewhurst DFA. It is aim to provides guidelines for the designer to design a product at the early design phase. The AD is aimed to identify the user needs. The user needs then, are translated into functional requirements and design parameters. At the design parameters, the TRIZ methodology is applied in order to produce several redesign alternatives. The best alternative is then, will be evaluating in terms of design for assembly. The case study is implemented on the table fan. It shows that, by using the develop methodology; the table fan would able to be assemble with lesser time.